Development of Super Deformed Digital Manga Comic Media Using Microsoft Paint to Improve Learning Outcomes and Learning Motivation of Junior High School Students on the Earth and Solar System Material - Alfarisi, Muhammad Fahmi; Mahardika, I Ketut; Narulita, Erlia (Integrated Science Education Journal, 2026)
Purpose of the study: Learning media used in teaching must increase student interest and motivation. An example is comics. This research on the development of digital super deformed manga comics has several objectives: to assess the media's validity, to test its practicality, and to test its effectiveness. Methodology: The research used is a type of Research and Development (R&D) research that provides validation of the developed product to be used in the learning process. The development model used in this study is the 4D model, which consists of 4 stages: defining (define), planning (design), developing (development), and disseminating (disseminate). Main Findings: The study achieved a validity level of 91.5% and was deemed valid. The results of the practicality of comic media in increasing learning motivation were 91.875% in the first school, 90.625% in the second school, and 92.5% in the third school. Meanwhile, the N-Gain scores indicating an increase in learning outcomes were 0.81 in the first school, 0.63 in the second school, and 0.69 in the third school. Novelty/Originality of this study: A super deformed digital manga comic was created using Microsoft Paint. This super deformed digital manga comic, in addition to using a chibi or super-deformed style, also imitates the drawing style of Masashi Kishimoto, the creator and writer of the Naruto series. This novel comic medium has successfully improved student learning outcomes and motivation.